2007
DOI: 10.2174/187221307780979892
|View full text |Cite
|
Sign up to set email alerts
|

Vcsa1 Gene Peptides for the Treatment of Inflammatory and Allergic Reactions

Abstract: The recently emerged Vcsa1 gene is one member of the variable coding sequence (VCS) multigene family of Rattus norvegicus. This gene encodes the precursor prohormone SMR1 (submandibular rat-1), which on enzymatic processing gives rise to several 5 to 11 amino acid peptides that modulate a variety of physiological functions. The analgesic pentapeptide sialorphin and anti-inflammatory heptapeptide submandibular gland peptide-T (TDIFEGG) are the most intensively studied. Although the Vcsa1 gene and its protein pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The predominant molecular form of CABS1 was detected at 27 kDa, and additional immunoreactive bands were also identified between 12 and 20 kDa and between 33 and 90 kDa in a small (13/99 and 10/99, respectively) number of participants. We originally identified CABS1 in human salivary gland extracts (71) during our search for a human protein with a sequence similarity to the anti-inflammatory peptide sequence near the carboxy terminus of the rat prohormone, SMR1 (36,44). The Smr1 gene we studied in rats is not present in humans, and although sequence similarity for other peptides derived from Smr1 with analgesic or erectile function activities had been identified in human PROL1 and SMR3A and SMR3B genes (73,74,79), the human gene with a sequence similar to the anti-inflammatory sequence from Smr1 was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant molecular form of CABS1 was detected at 27 kDa, and additional immunoreactive bands were also identified between 12 and 20 kDa and between 33 and 90 kDa in a small (13/99 and 10/99, respectively) number of participants. We originally identified CABS1 in human salivary gland extracts (71) during our search for a human protein with a sequence similarity to the anti-inflammatory peptide sequence near the carboxy terminus of the rat prohormone, SMR1 (36,44). The Smr1 gene we studied in rats is not present in humans, and although sequence similarity for other peptides derived from Smr1 with analgesic or erectile function activities had been identified in human PROL1 and SMR3A and SMR3B genes (73,74,79), the human gene with a sequence similar to the anti-inflammatory sequence from Smr1 was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It is processed also into other bioactive peptides, namely heptapeptide with the sequence TDIFEGG, named submandibular gland peptide-T and its C-terminal derivative, tripeptide FEG. The last mentioned above peptides are considered as regulators of inflammatory and allergic reactions in various animal models (Mathison et al 2010 ; Morris et al 2007 ). Sialorphin is released locally and systematically from SMR 1 protein.…”
Section: Inhibitors Of Enkephalin-degrading Enzymesmentioning
confidence: 99%
“…Rougeot et al ( 2003 ) have provided evidence that sialorphin is a natural inhibitor of the cell surface NEP in several mammals models. This indicates the lack of species-specific activity, similar to TDIFEGG peptide (Morris et al 2007 ). It has been demonstrated that this peptide acts as a competitive inhibitor of renal and spinal NEP, inhibiting the degradation of substance P and Met 5 -enkephalin and thus displaying analgesic activity (Rougeot et al 2003 ).…”
Section: Inhibitors Of Enkephalin-degrading Enzymesmentioning
confidence: 99%
“…Before considering the pharmacology of SGP-T and its analogues a brief summary of the VCSa1 gene family and its products is presented as this subject was recently reviewed [24]. …”
Section: Bioactivity Of Salivary Gland Extracts: Sgp-tmentioning
confidence: 99%
“…The VCSA family, containing the Vcsa1 gene, has emerged recently, and exclusively in rodents, whereas the proline-rich VCSB family is found in all placental mammals [27]. Human members of the VCSB family include PROL1 , SMR3B (PROL3) , and SMR3A (PROL5) [24], and encode salivary and lacrimal secreted proline-rich proteins [28-30]. The SMR1 protein product of the rat Vcsa1 gene is cleaved into at least two biologically active peptides, sialorphin (QHNPR) and SGP-T (TDIFEGG) (Figure 3).…”
Section: The Vcsa1 Gene Familymentioning
confidence: 99%